Evaluating corporate social responsibility engagement among small and medium enterprises using the theory of planned behaviour - Mohd Tan, Athirah (2019)
This study examined the relationship between a firm’s intention, the firm’s CSR activities as well as the outcomes from the CSR activities among Small and Medium Enterprises (SMEs) in Malaysia. By referring to the Theory of Planned Behaviour, this study not only examined the antecedents, such as participative leadership, risk orientation, stakeholders’ pressure and the firm’s facilitating conditions, of TPB factors (attitude toward behaviour, subjective norms and perceived behavioural control), it also analysed how attitude toward behaviour, subjective norms and perceived behavioural control affected the SME’s intention to engage in CSR causes. Besides that, this study examined the influence of an SME’s CSR intention on its CSR behaviour followed by the influence of the SME’s CSR behaviour on the firm’s performance. Lastly, this study also highlighted the moderating effect of the firm’s size on the relationship between the firm’s CSR behaviour and the firm’s performance. The research involved 1,545 listed SMEs and from which 362 questionnaires were solicited at the end of the data collection period. Partial Least Squares Structural Equation Modelling (PLS-SEM) approach was used to analyse the final data which were 301 questionnaires. The results of the analysis not only confirmed that all antecedents had a significant influence on the attitude toward behaviour, subjective norms, and the owner’s or manager’s perceived behavioural control, the three factors were also found to have a significant effect on the owner’s or manager’s intention to engage in CSR activities. The intention to engage in CSR activities was also found to be correlated with the owner’s or manager’s behaviour in performing the CSR activities, which was consequently reflected in the firm’s performance. By demonstrating a positive relationship between a firm’s CSR activities and its performance, this study adds to our understanding of the importance of CSR in SMEs. SMEs are therefore encouraged to focus more on marketplace CSR causes such as responsible marketing, responsible advertising, ethical and environmental standards of suppliers, treating suppliers as partners, as well as respecting and protecting customers to enhance performance. SMEs should also strengthen CSR policies for stakeholders as stakeholder pressure was shown to be important in this study. Other than that, suggestions can be made to policy makers in the Malaysian government to increase SMEs’ engagement in CSR activities by encouraging formalization of their CSR practices or introducing a flexible standard of resources for SMEs participation in CSR activities based on their size.